Use of reusable audiovisual elements as means to improve learning of Mathematics in Engineering: Experience based on teaching mathematics in engineering degrees - Casanueva Vicente, Ana; Bedia Jiménez, Joaquín; Sordo García, Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
After the COVID-19 pandemic, learning content virtualization has been promoted by educational institutions, leading to the development of audiovisual resources to support teaching. These materials often consist of videos of variable duration envisaged as a complement to other training strategies in order to facilitate the acquisition of specific learning contents. This work presents a collaborative experience among teachers for audiovisual content generation, tailored to the specific contents of different math-related basic subjects in five different engineering degrees at the University of Cantabria.